Pengaruh Buah Kurma Terhadap Durasi Persalinan Kala II Pada Ibu Bersalin - Siti Rossy Sunaryo; Herlina Simanjuntak (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2024)
During labor, the mother needs nutrition to produce energy during the labor process, the mother has sufficient energy. Dates are a food source that has energy-producing nutrients because they contain high levels of sugar. The aim of this research is to determine the effect of giving dates on the duration of the second stage of labor in women giving birth at the Friends of Rossy Medika Clinic in 2023. The type of quantitative research is quasy experimental with the research design being non equivalent control group design. The research population was 60 mothers in the second stage of labor. The sample that will be taken is 28 group respondents. The independent variable in this study was consumption of dates, while the dependent variable was the duration of the second stage of labor. The research was carried out at the Rossy Medika Friends Clinic located at Kp. Bojongsari, Sumbersari Village, Pebayuran District, Bekasi Regency, West Java in August 2023 - December 2023. Univariate analysis was used to determine the distribution of respondents' characteristics and the average duration of labor for the control and experimental groups, while bivariate analysis used the independent sample t-test with a sig (2-tailed) value of 0.001<0.005. Giving dates to the duration of the second stage of labor to women giving birth at the Rossy Medika Friends Clinic in 2023 the duration is faster than those who do not consume dates. The conclusion is that there is an effect of giving dates on the duration of the second stage of labor in mothers giving birth at the Rossy Friends Clinic in 2023.